Effects of Anti- Versus Pro-Vaccine Narratives on Responses by Recipients Varying in Numeracy: A Cross-sectional Survey-Based Experiment. (November 2017) - Bruine de Bruin, Wändi; Wallin, Annika; Parker, Andrew M.; Strough, JoNell; Hanmer, Janel
Background. To inform their health decisions, patients may seek narratives describing other patients' evaluations of their treatment experiences. Narratives can provide anti-treatment or pro-treatment evaluative meaning that low-numerate patients may especially struggle to derive from statistical information. Here, we examined whether anti-vaccine (v. pro-vaccine) narratives had relatively stronger effects on the perceived informativeness and judged vaccination probabilities reported among recipients with lower (v. higher) numeracy.Methods. Participants ( n = 1, 113) from a nationally representative US internet panel were randomly assigned to an anti-vaccine or pro-vaccine narrative, as presented by a patient discussing a personal experience, a physician discussing a patient's experience, or a physician discussing the experiences of 50 patients. Anti-vaccine narratives described flu experiences of patients who got the flu after getting vaccinated; pro-vaccine narratives described flu experiences of patients who got the flu after not getting vaccinated. Participants indicated their probability of getting vaccinated and rated the informativeness of the narratives.Results. Participants with lower numeracy generally perceived narratives as more informative. By comparison, participants with higher numeracy rated especially anti-vaccine narratives as less informative. Anti-vaccine narratives reduced the judged vaccination probabilities as compared with pro-vaccine narratives, especially among participants with lower numeracy. Mediation analyses suggested that low-numerate individuals' vaccination probabilities were reduced by anti-vaccine narratives—and, to a lesser extent, boosted by pro-vaccine narratives—because they perceived narratives to be more informative. These findings were similar for narratives provided by patients and physicians.Conclusions. Patients with lower numeracy may rely more on narrative information when making their decisions. These findings have implications for the development of health communications and decision aids.